2017
DOI: 10.1056/nejmoa1706198
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Gene-Replacement Therapy for Spinal Muscular Atrophy

Abstract: In patients with SMA1, a single intravenous infusion of adeno-associated viral vector containing DNA coding for SMN resulted in longer survival, superior achievement of motor milestones, and better motor function than in historical cohorts. Further studies are necessary to confirm the safety and efficacy of this gene therapy. (Funded by AveXis and others; ClinicalTrials.gov number, NCT02122952 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,608
0
44

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,870 publications
(1,772 citation statements)
references
References 23 publications
15
1,608
0
44
Order By: Relevance
“…The absence of such strong toxicity in the trial reported by Manno et al may be attributed to differences in vector serotype and dose (2e12 GC/kg versus 2e14 GC/kg). However, it is interesting to note that in a recent clinical trial for spinal muscular atrophy similarly large rAAV9 doses (2e14 GC/kg) were administrated intravenously and were well tolerated in a phase 1 [93], now progressing into a phase 3, clinical trial (ClinicalTrials.gov Identifier: NCT03505099). Although caution is warranted and necessitates further investigation, the response needs to be measured in order to put the wellbeing of patients first [94].…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…The absence of such strong toxicity in the trial reported by Manno et al may be attributed to differences in vector serotype and dose (2e12 GC/kg versus 2e14 GC/kg). However, it is interesting to note that in a recent clinical trial for spinal muscular atrophy similarly large rAAV9 doses (2e14 GC/kg) were administrated intravenously and were well tolerated in a phase 1 [93], now progressing into a phase 3, clinical trial (ClinicalTrials.gov Identifier: NCT03505099). Although caution is warranted and necessitates further investigation, the response needs to be measured in order to put the wellbeing of patients first [94].…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…ATAC combines FUS with replication-incompetent AAV vectors, an established method to stably transfect mammalian cells without integration into the target genome. AAV is widely used in neuroscience research, and has recently shown promise in the clinic [20][21][22][23][24] . When a gene of interest carried by AAV is encoded under an appropriate promoter, the expression of this gene can be restricted to a specific class of neurons 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In this short-term study, we did not observe CD4- or CD8-positive cell infiltration of treated muscle, but longer-term studies with more sensitive assays must be performed. Additionally, although production of large quantities of AAV9 poses a challenge, doses of 2 × 10 14 vg/kg have been successfully used in human gene therapy trials (35). …”
mentioning
confidence: 99%